Solid urban waste in the production of Aegiphila sellowiana Cham. seedlings - Marcos V. W. Caldeira; Fernando E. V. Santos; Sustanis H. Kunz; Valéria H. Klippel; William M. Delarmelina; Elzimar de O. Gonçalves (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of organic wastes as primary source of nutrients can contribute to reducing the dependence on inputs, besides being a sustainable destination for these materials. This study aimed to evaluate the quality of Aegiphila sellowiana seedlings grown in substrates composed of different proportions of sewage sludge, organic wastes and vermiculite. Twenty six substrates (treatments) were tested, formulated from the mixture of sewage sludge with vermiculite and the wastes coconut fiber, fresh coffee straw, organic compost (fresh bovine manure and fresh coffee straw), carbonized rice husk and fresh rice husk, at the proportions of 100:0, 80:20, 60:40, 40:60 and 20:80 (sewage sludge:materials), and a control, composed of commercial substrate (Bioplant®). At 120 days after sowing, the following morphological characteristics were determined: collar diameter, shoot height, dry matter (shoots, roots and total) and Dickson quality index (DQI) of all plants. Substrates formulated with sewage sludge and organic compost led to higher growth of seedlings (40% SS:60% OC and 20% SS:80% OC). Proportions of 20 to 40% sewage sludge and 60 to 80% organic compost are recommended for the production of A. sellowiana seedlings.